Charles Taylor and the Political Recognition of Difference as a Resource for Theological Reflection on Religious Recognition - Ryan, Gerard (Open theology, 2016)
This paper argues for a wider presentation of the term ‘recognition’ that includes ‘religion’ as a dimension of recognition. Toward this end, the author draws on the Canadian philosopher, Charles Taylor, who considered whether religion might be a supportive context for the promotion of recognition. Recognition for Taylor includes recognition not only of sameness, but, significantly, recognition of difference. As the author of this paper highlights, Taylor’s argument for recognition of difference is an important resource in any theological reflection on the possibility of religious recognition.